STUDY ON EFFECTIVE TEACHING STRATEGIES IN SHAPING THE EFFECTIVE ENTREPRENEURSHIP EDUCATION PROGRAM - Saxena, Arun (International Journal of Research -GRANTHAALAYAH, 2024)
Entrepreneurship plays a major role in economic development of the society and education is the most important pillar for the development of the nation. Thus, business schools and universities are paying their attention to promote entrepreneurship education programmes. But these programmes are being provided at numerous levels and there is a great need to assess the effectiveness of these programmes from different teaching strategies. Teaching strategy inevitability play an important role in this area and it can be considered as a good contribution in theory as well as in practice. Academic institutes can shape their entrepreneurship education programs with certain teaching strategies like Incubation and mentoring, Curricular and Co-curricular activities and understanding of multicultural perspective. The aim of this research is to find out the most effective teaching strategies to shape the entrepreneurship education program.